Thioredoxin-Interacting Protein Promotes Phagosomal Acidification Upon Exposure to Escherichia coli Through Inflammasome-Mediated Caspase-1 Activation in Macrophages - Yoon, Sung-Jin; Jo, Dong Hyun; Park, Seung-Ho; Park, Jun-Young; Lee, Yoo-Kyung; Lee, Moo-Seung; Min, Jeong-Ki; Jung, Haiyoung; Kim, Tae-Don; Yoon, Suk Ran; Chung, Su Wol; Kim, Jeong Hun; et al. (Frontiers in Immunology, 2019)
In host defense, it is crucial to maintain the acidity of the macrophage phagosome for effective bacterial clearance. However, the mechanisms governing phagosomal acidification upon exposure to gram-negative bacteria have not been fully elucidated. In this study, we demonstrate that in macrophages exposed to Escherichia coli, the thioredoxin-interacting protein (TXNIP)-associated inflammasome plays a role in pH modulation through the activated caspase-1-mediated inhibition of NADPH oxidase. While there was no difference in early phase bacterial engulfment between Txnip knockout (KO) macrophages and wild-type (WT) macrophages, Txnip KO macrophages were less efficient at destroying intracellular bacteria in the late phase and their phagosomes failed to undergo appropriate acidification. These phenomena were associated with reactive oxygen species production and were reversed by treatment with an NADPH oxidase inhibitor or a caspase inhibitor. In line with these results, Txnip KO mice were more susceptible to both intraperitoneally administered Escherichia coli and sepsis induced by cecum ligation and puncture than WT mice. Taken together, this study suggests that the TXNIP-associated-inflammasome-caspase-1 axis regulates NADPH oxidase to modulate the pH of the phagosome, controlling bacterial clearance by macrophages.